Designing an Interactive Digital Media to Support Higher Education Students’ English Spoken Communication Skill - Setiawan, Bondan; Arini, Restu (LPPM Universitas Mercu Buana Yogyakarta, 2021)
English communication, which has become an essential skill for graduates of the university, has not been achieved because of the low performance in spoken English proficiency. Offering necessary circumstances to support English learning during the outbreak of covid-19 is a challenge for educators in this digital age. This study addressed the emerging issue of the availability of media in online learning. It specifically aimed at designing interactive digital media that would not only assist the students in gaining the language skills but also develop their self-learning through its flexibility and accessibility. Design-based research was employed in the present study that involved the first-grade students of higher education. The ASSURE Model was used as a guideline for the appropriateness of the media, and a need analysis was conducted to find out the target and learning needs of the students through interview and questionnaires. The result showed that the design of interactive digital media gave positive impacts on the higher education students’ English communication skills and their independence in learning as well. The students’ performance was improved through pre-test and post-test results. The designed media itself was considered very good (a score of 87) by the seven aspects namely organization, speaking activities, appearance, learner-centered, content, feedback availability, and motivation impact.